PENGARUH PEMBELAJARAN BERBASIS ONLINE TERHADAP EFEKTIVITAS PEMBELAJARAN MAHASISWA AKUNTANSI UNISMA DI ERA WABAH COVID-19 - Muhammad Syahril Ramadhan; Nur Diana; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This research was conducted to determine the effect of online based learning on the effectiveness of accounting students at University of Islam Malang. This research is a type of research to the hypothesis and based on the type of relationship the variables studied are classified as correlational research. In the study, the authors took samples from active students of the University of Islam Malang, Accounting Study Program class of 2017, 2018, 2019 and 2020 who have taken online based learning in the era of the Covid-19. The sample calculation in this study used the slovin formula which resulted in 281 respondents. The data of analysis method used is simple linier regression. Based on the results of the test have been carried out, it is concluded that partial online based learning variables have an effect on the learning effectiveness of accounting students in the University of Islam Malang.Keywords: Online Based Learning, Learning effectiveness, Covid-19